Emergency airway management in Australian and New Zealand emergency departments: A multicentre descriptive study of 3710 emergency intubations2. (5th June 2017) - Alkhouri, Hatem; Vassiliadis, John; Murray, Matthew; Mackenzie, John; Tzannes, Alex; McCarthy, Sally; Fogg, Toby
Abstract: Objective: The aim of this study was to describe the practice of endotracheal intubation across a range of Australasian EDs. Methods: We established a multicentre airway registry (The Australian and New Zealand Emergency Department Airway Registry [ANZEDAR]) prospectively capturing intubations from 43 Australian and New Zealand EDs over 24 months using the ANZEDAR form. Information recorded included patient demographics, intubation indications, predicted difficulty, rapid sequence induction and endotracheal intubation preparation technique, induction drugs, airway adjuncts and complications. Factors associated with first attempt success were explored. Results: Of the 3710 intubations captured, 3533 were in adults (95.2%), 2835 (76.4%) for medical and 810 (21.8%) for trauma indications. Overall, 3127 (84.3%) patients were successfully intubated at the first attempt; the majority by ED doctors (2654 [72.1%]). A total of 10 surgical airways were performed, all of which were successful cricothyroidotomies. Propofol, thiopentone or ketamine were used with similar frequency for induction, and suxamethonium was the most often used muscle relaxant. Adverse events were reported in 964 (26%), the majority involving desaturation or hypotension. Conclusion: Australasian ED doctors, predominantly specialist emergency physicians or trainees, perform the majority of ED intubations using rapid sequence induction as their preferred technique mainly for medical indications. First attempt success rate was not different between different types of EDs, and is comparable published international data. Complications are not infrequent, and are comparable to other published series. Monitoring and reporting of ED intubation practice will enable continued improvements in the safety of this high‐risk procedure.